1975
DOI: 10.5962/bhl.title.87996
|View full text |Cite
|
Sign up to set email alerts
|

Softwood log exports and the value and employment issues /

Abstract: Direct employment per thousand board feet of logs processed is higher in domestic lumber and veneer and plywood industries than in the log export industry. Relative product values and indirect effects of domestic and export markets vary over time. Success of policies to maximize trade offs between markets is not certain because responses of industry members to changes in policies are uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Supplies and prices of domestic timber are only two of the concerns that have been raised in public discussions of policy on softwood-10g export. Other concerns are discussed in Hamilton (1971) and Darr (1975Darr ( , 1977 Cycles in housing starts and other end uses for lumber and plywood are reflected in cycles in lumber and plywood prices. Changes in end-product prices resulting from changes in demand are transmitted back to the timberresource base to interact with timber supplies to determine timber prices.…”
Section: Future Trade Prospects and Market Interactionsmentioning
confidence: 99%
“…Supplies and prices of domestic timber are only two of the concerns that have been raised in public discussions of policy on softwood-10g export. Other concerns are discussed in Hamilton (1971) and Darr (1975Darr ( , 1977 Cycles in housing starts and other end uses for lumber and plywood are reflected in cycles in lumber and plywood prices. Changes in end-product prices resulting from changes in demand are transmitted back to the timberresource base to interact with timber supplies to determine timber prices.…”
Section: Future Trade Prospects and Market Interactionsmentioning
confidence: 99%
“…The U.S. domestic log market did not demand high-quality stumpage materials, which helps explain why high-quality logs were diverted into the export market. Darr (1975a) found that log export volume was concentrated in the No. 2 and better saw log grades, whereas domestic sales were concentrated in the No.…”
Section: Year Log Exports (Billion Board Feet)mentioning
confidence: 99%
“…Many communities in the Pacific Northwest relied almost solely on timber harvesting and manufacturing of wood products for economic well-being, especially in rural areas where the local mill may be the only employer. Changes in log availability or market demand have a direct impact on economies with few alternative industries (Darr 1975a). Residents feared that overseas importers would divert large volumes away from domestic mills, causing mill closures and regional unemployment.…”
Section: Communities-mentioning
confidence: 99%
See 2 more Smart Citations